ESP FOR EFL: Roles and Methodology in ELT Class - Rahmi C. Lestari (ELT-Lectura, 2015)
Foreign Language Teachers for Specific Purposes have a lot in common with teachers of generalforeign language. For both it is necessary to consider linguistic development and teaching theories, to haveinsights in contemporary ideas regarding their own position and role as well as the position and role of foreignlanguage learners in education and to face new technologies offered as an aid to improve their methodology.The needs to understand the requirements of other professions and willingness to adapt to these requirementsdifferentiate the foreign language teachers for specific purposes and their colleagues teaching general foreignlanguage. ESP teaching presumes teaching of English as a foreign language regarding specific profession,subject or purpose.